Química ancestral africana: A origem da cachaça - Silva, Gustavo Henrique Costa da (2023)
We discuss, in this text, the creation of pinga in the sugar cane mills in the period of Colonial Brazil, from a legend that, in turn, presents conceptual errors that make the discovery of cachaça impossible, as pointed out in the “Legend of pinga”, which narrates the origin of this alcoholic beverage, a text used in the teacher training course at the Federal University of Uberlândia, in the Chemistry Degree course, when it was possible to apply it to legend and discuss the aforementioned errors contained therein, for through chemical and historical analyzes of the manufacturing processes of alcoholic beverages in Africa and Brazil, recovering the knowledge of indigenous, African and Afro-Brazilian peoples. In this way, we analyze episodes that were extracted from classes that took place in 2021 and 2022. Therefore, we present discussions that aim to diagnose the absence of ethnic-racial debates in education, as well as pointing to a problem, the Eurocentrism that has the organization social, political and economic, based on the centrality of Europe, silencing and erasing the technological contributions of indigenous, African and Afro-Brazilian peoples. We proposed, as a methodology, action-research, with the aim of verifying the processes of improvement in student learning and to enhance the classes in the subject "Introduction to Science and Technology of African Matrices", through ethnic-racial debates that demonstrate the ability of indigenous and black people to organize ideas and propose technological innovations. Therefore, in order to have teacher training with a view to ethnic-racial relations, we have shown that it is necessary to think of ways to question and problematize some contents that silence and distance the history and culture of indigenous, African and Afro-Brazilian peoples, because, for there is a breakdown of racism in society, it is imperative to train teachers with multicultural perspectives.